Relationship between foot morphology and biomechanical variables of the lower extremity joints during vertical jump - Park, S. H.; Park, S.-K. (Korean Journal of Sport Biomechanics, 2024)
Objective: The purpose of this study was to measure the morphological characteristics of the foot and biomechanical variables of the lower extremity joints during vertical jump and investigate the relationship between foot morphology and biomechanics of vertical jump. Method: 24 men in their 20s (age: 22.42 ± 1.41 yrs, height: 173.37 ± 4.61 cm, weight: 72.02 ± 6.21 kg, foot length: 251.70 ± 8.68 mm) participated in the study. Morphological characteristics of the foot included the length of the first toe, the length of the second toe, and the horizontal length from the center of ankle joint to the achilles tendon (Plantar Flexion Moment Arm [PFMA]). Biomechanical variables were measured for plantar flexor strength of the ankle joint and peak angular velocity, moment, and power of the lower extremity joint during vertical jump. Results: There was a significant correlation between the length of the first toe and plantar flexion strength at 30°/s [r=.440, p=.016], the angular velocity of the metatarsophalangeal [MTP] joint [r=-.369, p=.038] while significant correlations between PFMA and the angular velocities of the knee joint [r=.369, p=.038] and ankle joint [r=.420, p=.021] were found. There were also significant correlations between the length of the first toe and the maximum moment of the hip joint [r=.379, p=.034], and the length of the second toe and the power of the hip joint [r=-.391, p=.029]. Finally, significant correlations between PFMA and the power of the ankle joint [r=.424, p=.019] and MTP joint [r=.367, p=.039] were found. Conclusion: Based on the results of this study, the length of the toe and PFMA would be related to the function of the lower extremity joint. Therefore, this should be considered when designing the functional structure of a shoe. Furthermore, this relationship can be applied to intensive training for the plantar flexors and toe flexors to improve power in athletic performance.